The Stability Of Crank – Nicholson and Explicit Methods for Numerical Solution for Sine – Gordon Equation - Ramyi N. Ali; Awni M. Gaftan (Tikrit Journal of Pure Science)
In This Paper, We Solve The Sine – Gordon Equation by two Numerical Methods : Crank – Nicholson and Explicit and we discuss The Stabilities , and we obtained That The Stability Crank – Nicholson Methods is More Than The Stability Of Explicit Methods.